Joint meeting of the FAO panel of experts on pesticide residues in food and the environment and the WHO core assessment group, Geneve, Switzerland, 20 - 29 September 2004 (Rome, 2006)
This two-volume publication contains information on acceptable daily intakes (ADIs) and maximum residue levels, general principles for the evaluation of pesticides and the recommendations made at the 2005 Joint Meeting of the FAO Panel of Experts on Pesticide Residues in Food and the Environment (JMPR) and the WHO Core Assessment Group, which was held in Geneva, Switzerland in September 2005.
Keywords: Pesticide residues in food,Public health